Quantification of cyanogenic compounds, amygdalin, prunasin, and hydrocyanic acid in almonds (Prunus dulcis Miller) for industrial uses (2021)
The objective of this research was to quantify the concentration levels of the cyanogenic compounds, amygdalin and prunasin present in some varieties of almonds, considering their conversion to hydrocyanic acid, and their possible consumption in addition to other industrial uses, seeds of 29 commercial varieties were used of almond (Prunus dulcis Miller), evaluating its concentration and toxicity levels, taking into account the minimum degree of theoretical intake both for human consumption and for animals, through feed, this in terms of by-products. In addition, thermophysical properties thermophysical properties (thermal conductivity, thermal diffusivity, specific heat and density) and industrial uses were determined. The concentration was determined by chromatographic techniques (HPLC) and colorimetry (microdiffusion). The results obtained showed low levels of amygdalin from "not detected" to 375.40 mg/100 g of sample, depending on the sweet, slightly bitter and bitter varieties. The results indicate its possibility of commercialization, uses and applications in the food and pharmaceutical industry.